2013
DOI: 10.1128/ec.00096-13
|View full text |Cite
|
Sign up to set email alerts
|

A SAS-6-Like Protein Suggests that the Toxoplasma Conoid Complex Evolved from Flagellar Components

Abstract: SAS-6 is required for centriole biogenesis in diverse eukaryotes. Here, we describe a novel family of SAS-6-like (SAS6L) proteins that share an N-terminal domain with SAS-6 but lack coiled-coil tails. SAS6L proteins are found in a subset of eukaryotes that contain SAS-6, including diverse protozoa and green algae. In the apicomplexan parasite Toxoplasma gondii, SAS-6 localizes to the centriole but SAS6L is found above the conoid, an enigmatic tubulin-containing structure found at the apex of a subset of alveol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(111 citation statements)
references
References 87 publications
5
101
0
Order By: Relevance
“…A comprehensive analysis of centriole components conserved across eukaryotic organisms (12,13) showed that the T. brucei genome encodes a conserved SAS-6 homolog, which we named TbSAS-6 (Tb927.9.10550), in addition to a SAS-6-like protein (39). Despite a slightly larger size than its human homolog, TbSAS-6 contains two conserved motifs, a PISA (present in SAS-6) domain and a SAS-6 conserved domain 2, in its N terminus and four coiled-coil structures in the middle portion of the protein ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive analysis of centriole components conserved across eukaryotic organisms (12,13) showed that the T. brucei genome encodes a conserved SAS-6 homolog, which we named TbSAS-6 (Tb927.9.10550), in addition to a SAS-6-like protein (39). Despite a slightly larger size than its human homolog, TbSAS-6 contains two conserved motifs, a PISA (present in SAS-6) domain and a SAS-6 conserved domain 2, in its N terminus and four coiled-coil structures in the middle portion of the protein ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of these proteins alone is therefore not linked to the origin of parasitism, and their roles in parasites and free-living relatives cannot be assessed without direct functional evidence. Several proteins associated with the apical complex itself belong to this category, including rhoptry and microneme proteins (SI Appendix, Table S4) and cytoskeletal SAS6L (36). If chrompodellid homologs of these proteins are associated with structures for invasion or feeding, it would support the homology of these structures and the apical complex (37).…”
Section: /Namentioning
confidence: 99%
“…Centrioles and basal bodies are generally considered to be the same structure, although in Apicomplexa, the centriole (but not the basal body) has an unusual arrangement (15). Further evidence of the involvement of flagellar components in the apical complex was the characterization of a protein that locates to the basal plate of basal bodies in Trypanosoma brucei and to the apical end of the conoid in Toxoplasma (41). Significantly, all Apicomplexa have dispensed with flagella in life cycle stages that possess an apical complex.…”
Section: Discussionmentioning
confidence: 99%
“…The most intriguing feature of the apical complex of C. velia, given the recent findings on Toxoplasma (41,42), is that it is contemporaneous with the flagella in a single cell; in fact, there are multiple connections between the pseudoconoid and the anterior flagellum. A set of so-far-unidentified fibers connect the anterior flagellar groove to the apex of the pseudoconoid via an enigmatic coiled structure that resides beneath a protrusion of the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation